Linking Plant Diversity and Urban Uses at the City-Block Scale to Inform Urban Planning - Muriel Deparis; Nicolas Legay; Arthur Castellanos; Chloé Duque; Ulysse Guilloteau; Francis Isselin-Nondedeu; Sébastien Bonthoux (Land)
A challenge for urban ecology is to reduce biotic homogenisation by promoting plant diversity from local to city scales. As ecological and social components constantly interact in cities, an urban landscape characterisation reflecting socio-spatial functioning seems essential. However, spatially explicit description of cities at a relevant scale for urban planning are uncommon in ecological studies. Here, we explored a new approach based on the city-block scale, common in urban geography and planning, to directly link urban uses and patterns of herbaceous plant communities. We characterised all city blocks of a medium-sized French city (Blois). We inventoried grassland and meadows in 129 city blocks (10% of the whole city) for seven public and private urban uses (collective housing, individual housing, industrial, public service, park, land reserve, and road verge). We measured alpha diversity, community composition, regional originality of urban uses, and beta diversity between them. Urban land reserved for future development and parks harbour unique community composition within the city. Collective and individual housings have the same average alpha diversity, but the variability in community composition was higher for individual housing blocks. School and industrial city blocks have important alpha diversity and regional originality. Road verges have the highest alpha diversity but low regional originality and many common urban and regional species. Large green spaces with original communities should be protected during urban densification. The verticalization of residential housing could be an efficient means of internal urban densification if the lowest level of management intensity is promoted to maintain diversified vegetation. Some little-studied uses (schools, industrial city blocks) present opportunities to impede urban homogenisation.